The Village Funds and “Indeks Desa Membangun” (IDM) in Central Java Province - Fauzy Ade Priyatna; Indah Susilowati; Purnawan Adi Wicaksono (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Village funds are one of Indonesian Government's programs to encourage equitable development and improve economy starting from villages. The existence of village funds is expected to increase village independence which can be measured by IDM. IDM is a benchmark to provide an overview of village status through 5 classifications, namely very underdeveloped villages, underdeveloped villages, developing villages, developed villages, and independent villages. Village funds have a positive relationship with increasing IDM. This study aims to describe the role of village funds on IDM in Central Java Province. The research method used is a descriptive method with descriptive statistical analysis. The research data uses village funds budgets and IDM values of Central Java Province in the last 9 years (2015-2024). The study results show that there is a trend of increasing village funds budgets and IDM values in Central Java Province. The village funds budgets increased by around Rp 6.886.484.666.000,- between 2015 and 2024. Meanwhile, the IDM values increased by 0.1193 between 2016 and 2024. The increase in IDM values also encouraged a change in the status of IDM in Central Java Province from developing to developed. Based on these two trends, the increase of village funds budgets are in line with the increase of IDM values in Central Java Province. Thus, village funds have a positive role for IDM in Central Java Province.